The Theoretical Research on the Chiral Transition of Ibuprofen Molecules under Isolated Conditions (Journal of Atomic and Molecular Sciences, 2021)
In this article, we do a research on the chiral shift process of the isolatedalpha alanine molecule using the basis set of 6-31+g(d,p), which is based on densityfunctional theory B3LYP. Furthermore, the chiral transition path reaction potential energysurface of ibuprofen molecule is drawn by looking for the extreme value pointstructure including the transition state and intermediate. Finally, the geometry andelectronic structure properties of extreme value point are also analyzed. The resultsshow that there are two achieve reaction paths of ibuprofen from S-type to R-type.Path 1 consists of three transition states and two intermediate states. Path 2 includesfour transition states and three intermediate states. On the reaction path, the greatestbarrier which is from the transfer of hydrogen in chiral carbon to oxygen in carboxyl,is 73.54 Kcal/mol. The research provides a theoretical reference to further realize someimportant application value over the chiral transition reaction control of point chiralmolecule.
Keywords: Chiral; Ibuprofen; Density functional theory; Transition state.